Avaliação das características superficiais de instrumentos reciprocantes por meio de icroscopia eletrônica de varredura antes e após o uso - Hanan, Aida Renée Assayag [UNESP] (2014)
In order to evaluate by SEM, endodontic instruments reciprocating NiTi before and after use, considering debris, defects and deformations, twenty six instruments were divided into 2 groups, with 13 WaveOne® and 13 Reciproc®, which were micrographed with 150x magnification, after removal of the packaging. The files were used in the preparation of root canals of the mesial roots of extracted human mandibular molars. After, they were washed in ultrasonic tank and subjected to microscopic analysis to see new debris and deformations having as criteria the presence of irregular edge slot microcavity and burr. After the analysis using SEM and having the avaliators scores, the results were statistically compared using Kruskal-Wallis and Mann-Whitney's Tests, at a significance level of 5%. All instruments analyzed showed debris before and after use. There was a statistically significant difference regarding defects and deformations between groups (p <0.05). The presence of defects and deformities was higher in Waveone® instruments than Reciproc® instruments. It is essential that manufacturers of reciprocating endodontic instruments implement effective methods of surface finish in order to improve the quality of those favoring the success of endodontic treatment.